2020
DOI: 10.3390/rs12203426
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Selection Method Based on Partial Least Square from Hyperspectral Unmanned Aerial Vehicle Orthomosaic of Irrigated Olive Orchards

Abstract: Identifying and mapping irrigated areas is essential for a variety of applications such as agricultural planning and water resource management. Irrigated plots are mainly identified using supervised classification of multispectral images from satellite or manned aerial platforms. Recently, hyperspectral sensors on-board Unmanned Aerial Vehicles (UAV) have proven to be useful analytical tools in agriculture due to their high spectral resolution. However, few efforts have been made to identify which wavelengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 97 publications
1
17
0
Order By: Relevance
“…The average numbers of wavelengths selected by UVE and LW were 10, which was the smallest value. Some previous studies (Santos-Rufo et al, 2020;Xia et al, 2017) reported they greatly reduce variables but also remove some useful information and then this characteristic was confirmed in this study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The average numbers of wavelengths selected by UVE and LW were 10, which was the smallest value. Some previous studies (Santos-Rufo et al, 2020;Xia et al, 2017) reported they greatly reduce variables but also remove some useful information and then this characteristic was confirmed in this study.…”
Section: Discussionsupporting
confidence: 84%
“…UVE, LW and FiPLS generally had RPD values below 1.4 when the measured values merged after 100 iterations (Figure 2). Previous studies reported a reduced performance of FiPLS, LW and UVE because these methods removed useful information (Santos-Rufo et al, 2020;Xia et al, 2017). The reflectance at 550 nm, which is frequently noted as the green peak, was applied for estimating chlorophyll content in some studies (Carter & Knapp, 2001;Datt, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we adopted GA-PLSR whic allows a band selection procedure in PLSR [37]. There are numerous studies showing GA PLSR to be useful in promoting PLSR model performance [38,39]. It obeys the rule of bio logical evolution and natural selection to select informative features.…”
Section: Mapping Plant Community Traitsmentioning
confidence: 99%
“…This Special Issue includes advances based on RGB [3][4][5] multispectral [6], hyperspectral [7], LiDAR [8] and hyperspectral-LiDAR [9] sensors on-board UAVs, focusing on applications related to PA. These approaches applied various methodologies based on both images and cloud points.…”
Section: Overview Of Contributionsmentioning
confidence: 99%